Stefan problem for a weakly degenerate parabolic equation - Hryntsiv, N. M. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
In a domain with free boundary, we consider the inverse problem for the determination of time dependent coefficient of the first derivative of unknown fonction in a parabolic equation with weak power degeneration. As overdetermination conditions, the Stefan condition and the integral condition are given. Conditions for the existence and uniqueness of the classical solution of considered problem are established.